FACTO Dataset: A Dataset of User Reports for Faulty Computer Components - Silva, Maria de Lourdes M.; Mendonça, André L. C.; D. Neto, Eduardo R.; Chaves, Iago C.; Caminha, Carlos; Brito, Felipe T.; Farias, Victor A. E; Machado, Javam C. (Anais do Dataset Showcase Workshop (DSW); 2024: Anais do VI Dataset Showcase WorkshopDO - 10.5753/dsw.2024.243802, 2024)
Advancements in electronic fabrication technologies have facilitated the large-scale production of computer components, which are prone to faults over time. Despite the availability of fault-reporting tools provided by hardware manufacturers, there is a significant gap in effectively utilizing textual reports due to data scarcity. In this paper, we introduce FACTO dataset, a comprehensive collection of user reports on faulty computer components such as video cards, storage devices, motherboards, memory, and others. Data was gathered through a survey of hardware specialists, web scraping of internet forums, and synthetic text generation from real manufacturer data using large language models. This dataset aims to provide insights for correlating user reports with faulty components, thus enhancing diagnostic capabilities and improving hardware reliability and customer satisfaction.